Diplomatic Dilemma dan Standar Ganda Politik Amerika Serikat Terhadap Konflik Sipil-Militer Mesir Tahun 2013 - Setiawan, Azhari (Jurnal Hubungan Internasional, 2015)
United States of America as the main actorâin many casesâof world politics constellation has done a number of double standard politics for preserving its certain national interest. For a century, Middle East has been one of the most focussed object for United States foreign policies. This research is aimed to explain United States diplomatic dilemma and double standard politics toward Egypt civil-military conflict and Morsi coup in 2013, which tries to answer why United States used double standard politics on Egypt case. United States never calls Egypt case as a coup and still continuing its foreign aid to Egyptâs new governement (military government). Researcher has formulated an answered-hypothesis which reveals the facts that United States double standard is caused by United States diplomatic dilemma. These diplomatic dilemmas also influenced by United States pragmatism on its Arab Spring foreign policy.